2016
DOI: 10.1016/j.radphyschem.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced reduction–polymerization route for the synthesis of PEDOT conducting polymers

Abstract: Synthesis of conducting poly(3,4-ethylenedioxythiophene), PEDOT, is achieved through an original reductionpolymerization route: γ-radiolysis of aqueous solutions containing EDOT monomers under N 2 atmosphere. According to UV-vis absorption spectrophotometry and ATR-FTIR spectroscopy, reduction of EDOT is initiated by hydrated electrons produced by water radiolysis and leads to PEDOT polymers through coupling reactions. The morphology of PEDOT is characterized by Cryo-TEM microscopy in aqueous solution and by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…After measuring the thickness of the film by a surface profiler, its conductivity was determined by the fourpoint probe technique and found to be 2.6 Â 10 À3 S cm À1 . The conductivity of the PEDOT polymers synthesized by radiolysis in DCM is then close to the conductivities of PEDOT polymers we earlier synthesized by high energy radiation (gamma-rays or accelerated electrons) in aqueous solution 18,20 and remains close to those already reported in the literature for PEDOT polymers produced by conventional synthetic methods. 36,46 The measurements and characterizations made by thermogravimetric analysis, cyclic voltammetry and the four-point probe technique enable us to conclude that PEDOT polymers synthesized in dichloromethane by our alternative radiolytic method have not only a good thermal stability but also present interesting electronic properties (band gap and conductivity), which are comparable to those reported in the literature for PEDOT polymers synthesized by chemical or electrochemical methodologies.…”
Section: Physicochemical and Electrochemical Performances Of Radiosynsupporting
confidence: 85%
See 1 more Smart Citation
“…After measuring the thickness of the film by a surface profiler, its conductivity was determined by the fourpoint probe technique and found to be 2.6 Â 10 À3 S cm À1 . The conductivity of the PEDOT polymers synthesized by radiolysis in DCM is then close to the conductivities of PEDOT polymers we earlier synthesized by high energy radiation (gamma-rays or accelerated electrons) in aqueous solution 18,20 and remains close to those already reported in the literature for PEDOT polymers produced by conventional synthetic methods. 36,46 The measurements and characterizations made by thermogravimetric analysis, cyclic voltammetry and the four-point probe technique enable us to conclude that PEDOT polymers synthesized in dichloromethane by our alternative radiolytic method have not only a good thermal stability but also present interesting electronic properties (band gap and conductivity), which are comparable to those reported in the literature for PEDOT polymers synthesized by chemical or electrochemical methodologies.…”
Section: Physicochemical and Electrochemical Performances Of Radiosynsupporting
confidence: 85%
“…14 Apart from the traditional methods of polymers synthesis, ionizing radiation induced polymerization by g-rays or accelerated electrons is not commonly used in the field of CP synthesis. 15 In previous studies, our group has developed a new methodology based on radiation chemistry to polymerize some of those conducting polymers in aqueous solutions [16][17][18][19] thanks to the oxidation of dissolved organic monomers by oxidizing radicals in situ produced in the medium during water radiolysis. Additionally, pulse radiolysis was used to study and to understand the growth mechanism of PEDOT polymers initiated by these radicals in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…There are several synthetic pathways for aniline oxidation and different types of nanostructure production, which lead to the formation of different phases for PANI. The most popular methods are chemical oxidation [11], template methods [12], and electrochemical processes [13], with less popular methods involving sonochemical [14] or radiation approaches [15]. Dhawale et al have reported a specific capacity of 503 F g −1 for bulk PANI synthesized via a chemical bath deposition method measured at a sweep rate 10 mV s −1 in 1 M of H 2 SO 4 [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, improvements in instrumentation and data analytics have facilitated a paradigm-shift in correlative multimodal microscopy. For example, scanning probe microscopy in combination with other spectroscopical methods allows acquisition of localized physical properties for a wide range of materials, which can be used to characterize local chemical composition yielding unique insights into the structure-property relationship of functional materials, 1,2 novel composites, 3,4 and biological objects. [5][6][7][8] This approach involves datasets where spatial coordinates may be augmented with one or more spectroscopic dimensions.…”
Section: Introductionmentioning
confidence: 99%